Creating more just cities: The right to the city and capability approach combined - Séverine Deneulin (University of Bath, Centre for Development Studies (CDS), 2014)
Eighty percent of the Latin American population is now urban, but the urbanization process has been accompanied by greater inequality and social segregation. To address urban exclusion, the idea of 'the right to the city' is increasingly being endorsed by international organizations and national governments as conceptual framework for urban policy towards more inclusive cities. The paper argues that the right to the city is a limited framework to revert the fragmentation trend of the Latin American city, and it examines how the capability approach could offer more suitable conceptual tools to that effect. The paper proposes the idea of 'just cities for life' as the outcome of a combination of the right to the city and a capability-view of justice. It explores some avenues for translating the idea into concrete actions to create cities in which all residents can equally have opportunities to live well in the urban space they share.
Keywords: 330; Latin America; urban inequality; social justice; Amartya Sen; capability approach